Vegetables for better nutrition and safe environment - Singh, Jagdish; Behera, T K; Singh, A K (Indian Horticulture, 2022)
Vegetable crops are a vital component of agriculture for ensuring food and livelihood security owing to their higher yield potential and better nutrient contents. Enormous diversity in vegetables cater to the dietary nutrient requirements of humans and therefore vegetables make a very important constituent of food for fulfilling nutritional security as well. Most of the vegetables are short duration crop easily adjusted in crop diversification, provide higher biomass and return leading to nutritional and economic security to resource-poor farmers. Vegetables are also economic engines for productive, profitable agricultural economies. Intensified vegetable production has the potential to generate more income and employment than other segments of the agricultural economy, making vegetables an important element of any agricultural growth strategy. Vegetable production provides a promising economic opportunity for reducing rural poverty and unemployment in rural areas, and is a key component of farm diversification strategies.